Bibliotherapy on Self Concept in Children with Mental Retardation - Seprita, Afdalya Ibna; Permanasari, Ika; Amin, Suci (Poltekkes Kemenkes Semarang, 2024)
Background: the social limitations experienced by children with disabilities cause them to have a negative self-concept. One of the therapies that can be used to improve self-concept is bibliotherapy.Purpose: the purpose of this study was to determine the effect of bibliotherapy on self-concept in children with mental retardation.Methods: the design used in this research is quasy experimental design, the researcher used one group pretest-posttest. The population in this study were all children with disabilities in SLB Negeri Pembina Pekanbaru, namely grade 5 elementary school students totaling 14 students. The sample in this study was selected by non-random (non probability) sampling, namely total sampling, Data obtained from the distribution of the Robson Self-Concepts Scale questionnaire to assess self-concept in children with disabilities. The statistical test used is the Wilcoxon Rank Test.Results: the univariate results in this study obtained the median value for respondent characteristics based on age 12.00 while characteristics based on gender are respondents with male gender as many as 9 respondents (64.3%). Bivariate results using the Wilcoxon Rank Tast test, obtained p value = 0.001 ˂ 0.05.Conclusion: bibliotherapy has an effect on improving self-concept in children with tunagrahita. It is expected that schools and parents can apply bibliotherapy to improve self-concept in children with mental retardation.